2021
DOI: 10.1371/journal.pone.0250434
|View full text |Cite
|
Sign up to set email alerts
|

Implementation outcomes of HIV self-testing in low- and middle- income countries: A scoping review

Abstract: Introduction HIV self-testing (HIV-ST) is an effective means of improving HIV testing rates. Low- and middle-income countries (LMIC) are taking steps to include HIV-ST into their national HIV/AIDS programs but very few reviews have focused on implementation in LMIC. We performed a scoping review to describe and synthesize existing literature on implementation outcomes of HIV-ST in LMIC. Methods We conducted a systematic search of Medline, Embase, Global Health, Web of Science, and Scopus, supplemented by sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 208 publications
(317 reference statements)
5
34
0
Order By: Relevance
“…HIV self-testing has been touted as the game-changer in HIV testing uptake with high HIV testing rates reported in studies conducted in low and middle-income countries, a majority of which were conducted in sub-Saharan Africa ( 1 ). In this highly successful Research Topic, we assessed the power of HIV self-testing in reaching unreachable populations in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…HIV self-testing has been touted as the game-changer in HIV testing uptake with high HIV testing rates reported in studies conducted in low and middle-income countries, a majority of which were conducted in sub-Saharan Africa ( 1 ). In this highly successful Research Topic, we assessed the power of HIV self-testing in reaching unreachable populations in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread use of self-testing for SARS-CoV-2 infection could help improve the control of the spread of the SARS-CoV-2 epidemic [ 16 , 17 , 18 , 19 , 20 , 21 ]. Previous experience with HIV self-testing showed that a self-test can be performed perfectly well by a layperson and gives reliable and accurate results, and that HIV self-testing is considered as an acceptable and useful tool to improve HIV testing coverage worldwide to improve HIV epidemic control [ 22 , 23 ]. Lateral flow tests for the SARS-CoV-2 antigen are appropriate for use as an antigen-detecting rapid diagnosis self-test (Ag-RDST) because of their low cost, ease of use, and prompt result [ 12 , 14 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…If this is the case, then the oral HIVST has the potential to speed up testing behaviour and balloon the number of people aware of their HIV status. In addition, the large majority indicating that they would prefer to perform the HIVST at home, implies that HIVST can be an attractive way to reach large numbers of the population who may be anxious about undergoing initial tests in more public facilities such as clinics [30].…”
Section: Discussionmentioning
confidence: 99%